Implementasi Kebijakan Berbasis Blue Economy Dalam Kerangka Kerja Sama Pemerintah Indonesia Dengan Food And Agriculture Organization (Fao): Studi Mengenai Unit Pengolahan Ikan (UPI) Di Kabupaten Lombok Utara - Yundari Amelia Chandra; Ismah Rustam; Purnami Safitri (Indonesian Journal of Global Discourse, 2021)
This research discusses about how Indonesia implements the Blue Economy concept based marine policy in the collaboration between the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia (KKP-RI) with the Food and Agriculture Organizations of the United Nations (FAO) to collaborate on the “Development of Effective and Inclusive Development project program Food Value Chains in ASEAN Member States” held during 2018-2019 in North Lombok Regency. The purpose of this study is to analyze the cooperation that takes place between MMAF-FAO using the concept of global governance and how the implementation of the concept of blue economy in Indonesia. In addition, this research also looks at how this collaboration affects the economic, environmental and social aspects of the community, especially project managers.